Ranking of national teams in the men's 50 km cross-country skiing based on the analysis of team and individual achievements at the olympic winter games and world championships - Shvetsov, A.V.; Chubanov, E.V.; Belyaeva, N.A.; Sirakovskaya, Ya.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the rating of national teams in the ski race 50 km in men based on the analysis of team and personal achievements at the Olympic Winter Games and World Championships. Methods and structure of the study. Analysis, generalization and comparison was attached to the achievement of the winners in a 50 km race at all major tournaments held in the entire history of ski racing. Results and conclusions. It has been established that out of 136 skiers who became winners of title tournaments, only 25 managed to do it twice or more, which confirms the fact about the specificity of the preparation and complexity of the ski marathon. The research results revealed that among national teams two-thirds awards (68%) on the account of Skiers of Sweden, Norway and Finland. Racers from the USSR and Russia occupy the fourth place in this list (12.5%). Achievements of domestic athletes on the last OzI and the World Cup are a reason to believe that at the present stage of the development of ski racing, Russian skiers will remain the main competitors in the struggle for prizes in a 50 km race with riders from Northern Europe and other countries.